2022
DOI: 10.3389/fmats.2022.925321
|View full text |Cite
|
Sign up to set email alerts
|

3D Bioprinted Scaffolds for Tissue Repair and Regeneration

Abstract: Three-dimensional (3D) printing technology has emerged as a revolutionary manufacturing strategy that could realize rapid prototyping and customization. It has revolutionized the manufacturing process in the fields of electronics, energy, bioengineering and sensing. Based on digital model files, powdered metal, plastic and other materials were used to construct the required objects by printing layer by layer. In addition, 3D printing possesses remarkable advantages in realizing controllable compositions and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 142 publications
0
12
0
Order By: Relevance
“…5 Therefore, the 3D printed scaffolds/bioprinted tissues should possess features such as (i) cell binding motifs, (ii) porous structure for proper diffusion of nutrients and cell migration, (iii) mechanical stability, (iv) biodegradability at a defined rate and (v) biocompatibility (nonimmunogenic/non-toxic) to promote clinical translation. 6 The TE field often endeavours to develop functional tissue grafts by culturing tissue-equivalent structures in a static in vitro culture environment. Static culture condition can only provide adequate cell maturation in the scaffold with limited tissue functionalization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Therefore, the 3D printed scaffolds/bioprinted tissues should possess features such as (i) cell binding motifs, (ii) porous structure for proper diffusion of nutrients and cell migration, (iii) mechanical stability, (iv) biodegradability at a defined rate and (v) biocompatibility (nonimmunogenic/non-toxic) to promote clinical translation. 6 The TE field often endeavours to develop functional tissue grafts by culturing tissue-equivalent structures in a static in vitro culture environment. Static culture condition can only provide adequate cell maturation in the scaffold with limited tissue functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…5 Therefore, the 3D printed scaffolds/bioprinted tissues should possess features such as (i) cell binding motifs, (ii) porous structure for proper diffusion of nutrients and cell migration, (iii) mechanical stability, (iv) biodegradability at a defined rate and (v) biocompatibility (non-immunogenic/non-toxic) to promote clinical translation. 6…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The ultimate requirement of any scaffold in bone tissue engineering is to demonstrate its efficacy in forming a predictable quantity of good quality bone. 3 The unique arrangement of trabecular structures influences tissue properties at various levels from cellular behavior to biomechanical performance. Cells within these architectures experience diverse microenvironments, affecting their proliferation, differentiation, and overall function.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The ultimate requirement of any scaffold in bone tissue engineering is to demonstrate its efficacy in forming a predictable quantity of good quality bone . The unique arrangement of trabecular structures influences tissue properties at various levels from cellular behavior to biomechanical performance.…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39] Some studies have successfully fabricated 3D nanofiber aerogel scaffolds and demonstrated their ability to enhance bone regeneration and repair. [40][41][42] Compared with nanofiber membranes, aerogels have larger pores, which can promote the adhesion and migration of bone cells and promote bone repair and regeneration to a greater extent. In addition, research is being conducted on the preparation of guided bone regeneration scaffolds with biofunctions, particularly the antibacterial and osteogenesis capabilities.…”
Section: Introductionmentioning
confidence: 99%